The Effect of Labor Market Conditions on Retirement Decisions - Dong, Xu. (Tufts University. Tisch Library., 2019)
How older workers make their retirement decisions and what factors have a strong influence on decision making is always a popular topic. This paper attempts to examine how labor market conditions, a less studied factor, affect retirement decision making. It also attempts to examine the existence of heterogeneous effect among age groups and industries. The author defines six possible retirement transition categories, and uses these six outcomes to construct a multinomial logit model. Using data from Health and Retirement Study, we find that older workers below 62 are more likely to stay in the labor force and less likely to either completely or partly retire. No evidence is found for heterogeneous labor market effects by age group. Many industries consistently demonstrate strong labor force attachment, while two industries showing weaker attachment and higher probability to retire. Only two industries do not demonstrate clear patterns regarding labor force attachment.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Economics.; Advisor: Melissa McInerney.; Committee: Alan Finkelstein Shapiro.; Keyword: Labor economics.